Chemical control of morning glory as a function of water restriction levels - Giancotti, P.r.f. [UNESP] (2014)
Among the herbicides recommended for the dry season and registered to sugarcane crop, amicarbazone, isoxaflutole and the association diuron + hexazinone + sulfomethuron-methyl can be highlighted. These are pre-emergence herbicides efficient against broad-leaved weeds. Morning glory causes large losses in infested sugarcane fields by bending the stalks and interfering in harvesting. In this study the effectiveness of pre-emergence herbicides for two species of morning glory (Ipomoea hederifolia and Ipomoea grandifolia) was evaluated. Treatments were arranged in completely randomized factorial design (4 x 7). There were four periods of water restriction (0, 30, 60 and 90 days), seven chemical treatments [diuron + hexazinone + sulfometuron-methyl (1387 + 391 + 33.35 g a.i. ha-1), diuron + hexazinone + sulfometuron-methyl (1507.5 + 425 + 36.25 g a.i. ha-1), diuron + hexazinone + sulfometuron-methyl (1658.25 + 467.5 + 39.87 g a.i. ha-1), diuron + hexazinone + sulfometuronmethyl (1809 + 510 + 43.5 g a.i. ha-1), amicarbazone (1190 g a.i. ha-1), amicarbazone + isoxaflutole (840 + 82.5 g a.i. ha-1)] and a control with no application. At 7, 14, 21 and 28 days after the restoration of moisture, control was visually evaluated. After the final evaluation, the dry mass of morning glories was measured. At 90 days of water restriction, diuron + hexazinone + sulfometuron-methyl was more effective to control I. hederifolia than the amicarbazone + isoxaflutole tank mixture. The four diuron + hexazinone + sulfometuronmethyl doses have reduced morning glory dry mass to zero; whereas treatments with amicarbazone have not. The most effective treatment for morning glory control was diuron + hexazinone + sulfometuron-methyl. This result may be due to a possible synergistic interaction.